Trajectory of shuttlecock using Newton’s Second Law / Nur Athirah Nurul Azam, Saibatul Asmaliah Amran and Nur Farahin Eliana Mohd Nooraimy - Nurul Azam, Nur Athirah; Amran, Saibatul Asmaliah; Mohd Nooraimy, Nur Farahin Eliana (2023)
Sports like badminton require skilled performance to coordinate dynamic interceptive actions to place the racket in the proper location at the correct moment to intercept the shuttlecock (projectile) and protect or attack court space. The problem statement on this study is the player needs to focus on the service angle before releasing the shuttlecock to maximise the distance the shuttlecock falls on the opposing team's court to obtain the point. The player needs to strengthen their ability to read their opponent's shots and it might be difficult for the player to figure out and predict the angles that need to be produced so that the opponent player has difficulty receiving the shot.